Telegram, 1932 May 20, New York, N.Y., to Amelia Earhart, H. Grace, Nf. - Putnam, George Palmer, 1887-1950 (Purdue University Libraries, Archives and Special Collections, 1932)
George Palmer Putnam telegraph to Amelia Earhart at Harbor Grace, Newfoundland, regarding weather conditions, May 20, 1932